Pengaruh Latihan Range Of Motion Pada Ekstremitas Atas Dengan Genggam Bola Karet Terhadap Kekuatan Otot Pasien Stroke (Studi Literature) - imelda appulembang; I Made Sudarta (Sekolah Tinggi Ilmu Kesehatan Gunung Sari, 2022)
Background: Stroke is an acute neurological function disorder caused by a sudden disturbance of cerebral blood circulation (within a few seconds) or quickly (within a few hours) symptoms and signs arise according to the focal area in the brain that is disturbed. This occurs when the blood supply to part of the brain stops. The World Health Organization (WHO) in 2016 said that stroke was ranked second as a non-communicable disease that caused death. Stroke is also the third leading cause of disability worldwide. The prevalence of stroke in Indonesia based on the diagnosis of health workers or symptoms is 7% and increased in 2018 by 10.9%. Problems related to immobilization conditions in stroke patients are stated as nursing diagnoses. The main nursing diagnosis in accordance with the problem of immobilization in stroke patients is impaired physical mobility. One form of physiotherapy to restore muscle strength is Range Of Motion (ROM). Research Objectives: To determine the management of ROM and rubber ball grip exercises in stroke patients with impaired physical mobility. Research Methods: This is a literature study that summarizes several theoretical references and journals related to the theme. Results: From the eight articles, it showed that there was an effect on increasing muscle strength after ROM exercises and hand-held exercises with rubber balls. Conclusion: From these eight articles, it was shown that ROM exercises and hand-held exercises with rubber balls were effective in increasing muscle strength in stroke patients.